Childhood Cancers Misdiagnosed as Tuberculosis in a High Tuberculosis Burden Setting. Issue 12 (December 2021) - van Heerden, Jennifer K.; van Zyl, Anel; Schaaf, Hendrik Simon; Frigati, Lisa J.; Goussard, Pierre; Rabie, Helena
Abstract : Background: Tuberculosis (TB) and childhood cancers have overlapping presentations and malignancies may be misdiagnosed as TB in high TB-burden settings. Methods: This retrospective study investigated the diagnosis of TB in children with cancer registered in the Tygerberg Hospital Childhood Tumor Registry from 2008 to 2018. We studied children on anti-tuberculosis treatment (ATT) at cancer diagnosis or diagnosed with TB within 1 month of cancer diagnosis. We describe the circumstances and extent of this misdiagnosis, quantify the delay in therapy and document the outcomes of these children. Results: Twenty-seven of 539 (5%) children in the registry started ATT before cancer diagnosis. Both pulmonary and extrapulmonary TB complicated the cancer diagnosis. Of the 27 patients on ATT at cancer diagnosis, 22 (81%) had contact with a TB case and in 6 of 12 children (50%) a tuberculin skin test was positive. At cancer diagnosis, 16/27 (59%) children had chest radiograph changes interpreted as TB with 11/27 (41%) regarded as suggestive of TB on expert review. The median diagnostic delay between TB and cancer diagnoses was 25 days (interquartile range 3.5–58). Of 539 children with cancer, 204 (38%) died of cancer, including 18/30 (60%) children on ATT at cancer diagnosis or diagnosed with TB within 1 month of cancer diagnosis (odds ratio 2.6; 95% confidence interval: 1.2–5.4; P = 0.012). Conclusions: The clinical and radiologic overlap of TB and cancer causes diagnostic confusion in a significant number of children with cancer and may contribute to increased mortality. Abstract : Supplemental Digital Content is available in the text.